Cloud Services Usage Profile Based Intruder Detection and Prevention System: Intrusion Meter - Annappaian, Dinesha Hagare; Agrawal, Vinod Kumar (Discoveries in Agriculture and Food Sciences, 2015)
With the emerging usage of cloud computing services, the misuse of possible vulnerabilities grows at the same speed. The distributed nature, on demand services, wide usage of the cloud computing makes it an attractive target for potential intruders. Intruders are the network security attackers intend to breach cloud security. Despite security issues delaying cloud adoption, cloud computing has already become an inescapable needs and ready industry solutions. Thus, security mechanisms to ensure its secure adoption are in demand. One security mechanism is intrusion detection and prevention systems (IDPS). IDPS have been used widely to detect malicious behaviors in network communication and hosts. Here, we focus on IDPS to defend against the cloud intruders. We propose a technique called cloud service usage profile based IDPS technique. This technique is to detect and prevent intruders in cloud service intrusion based on the cloud service usage profile. In turn, this usage profile helps to detect unusual usage and prevent intrusion.